2020
DOI: 10.3389/fphar.2020.00430
|View full text |Cite
|
Sign up to set email alerts
|

The Skeletal-Protecting Action and Mechanisms of Action for Mood-Stabilizing Drug Lithium Chloride: Current Evidence and Future Potential Research Areas

Abstract: Lithium, the lightest natural-occurring alkali metal with an atomic number of three, stabilizes the mood to prevent episodes of acute manic and depression. Multiple lines of evidence point to lithium as an anti-suicidal, anti-viral, anti-cancer, immunomodulatory, neuroprotective and osteoprotective agent. This review article provides a comprehensive review of studies investigating the bone-enhancing effects of lithium and its possible underlying molecular mechanisms. Most of the animal experimental studies rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 95 publications
1
24
0
Order By: Relevance
“…Consistent with observations in ovariectomized rats, LiCl significantly reduced orthodontic tooth movement in rats [9] and attenuated force-induced root resorption [10]. The molecular mechanism remains unclear but may be attributed to a positive balance of bone turnover that also helped to compensate for bone loss and stimulates osseointegration in ovariectomized rats [11] involving the Wnt/β-catenin and other signaling pathways [12]. Importantly, biomechanical activation of the Wnt/β-catenin pathway in osteocytes involves nitric oxide production [13] and in OTM, these are the osteocytes that become the major promotors to mediate osteoclastogenesis and to regulate bone formation.…”
Section: Introductionsupporting
confidence: 73%
“…Consistent with observations in ovariectomized rats, LiCl significantly reduced orthodontic tooth movement in rats [9] and attenuated force-induced root resorption [10]. The molecular mechanism remains unclear but may be attributed to a positive balance of bone turnover that also helped to compensate for bone loss and stimulates osseointegration in ovariectomized rats [11] involving the Wnt/β-catenin and other signaling pathways [12]. Importantly, biomechanical activation of the Wnt/β-catenin pathway in osteocytes involves nitric oxide production [13] and in OTM, these are the osteocytes that become the major promotors to mediate osteoclastogenesis and to regulate bone formation.…”
Section: Introductionsupporting
confidence: 73%
“…However, small molecules intervening in different compounds may overcome this problem and offer therapeutic potential [ 3 ]. One of these molecules is lithium, which has promising effects on bone healing and inhibits GSK3β, thereby activating Wnt/β-catenin [ 34 , 35 ]. Although the therapeutic effect of lithium in promoting bone healing has been well documented in experimental settings and clinical trials, its major medical limitation is still its clinical underutilization, which is attributable to its unfavorable side effects [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the stimulatory effects of Wnt/β-catenin signaling on osteoblast differentiation has previously been wellestablished (32), the effects of LiCl on osteogenesis remains controversial. Several studies have shown the positive effects of LiCl on osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%